2018
DOI: 10.2147/ott.s160014
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of hormone receptors, Ki-67, endoglin (CD105), claudins 3 and 4, MMP -2 and -9 in endometrial polyps and endometrial cancer type I

Abstract: ObjectiveThe aim of this study was to investigate the malignant potential of endometrial polyps (EP) by assessing the immunoexpressions of both estrogen receptor (ER) and progesterone receptor (PR), Ki-67 cell proliferation index, neovascularization network (endoglin – CD105), cellular adhesion molecules (claudins 3 and 4), and extracellular matrix proteins (MMP-2 and -9) in both EP and endometrioid adenocarcinoma (type I) in comparison with the normal endometrium.Study designThis is a cross-sectional comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Furthermore, its prognostic value seems to be complementary or even better to the routinely applied molecular markers, such as CD34, used to visualize tumor advancement [242][243][244][245][246][247][248] (Table 1). Interestingly, there are no significant differences in endoglin staining between endometrial polyps and endometrial adenocarcinomas, which supports the fact that neovascularization is associated both with hyperplastic and neoplastic lesions of the endometrium [249]. On the other hand, the preoperative serum levels of endoglin in patients with endometrial carcinoma show poor performance as a diagnostic marker of tumor metastasis [250].…”
Section: Tgfβ Signal Modulation Can Be Altered By Impaired Co-receptors Expressionmentioning
confidence: 64%
“…Furthermore, its prognostic value seems to be complementary or even better to the routinely applied molecular markers, such as CD34, used to visualize tumor advancement [242][243][244][245][246][247][248] (Table 1). Interestingly, there are no significant differences in endoglin staining between endometrial polyps and endometrial adenocarcinomas, which supports the fact that neovascularization is associated both with hyperplastic and neoplastic lesions of the endometrium [249]. On the other hand, the preoperative serum levels of endoglin in patients with endometrial carcinoma show poor performance as a diagnostic marker of tumor metastasis [250].…”
Section: Tgfβ Signal Modulation Can Be Altered By Impaired Co-receptors Expressionmentioning
confidence: 64%
“…Previous studies have shown increased expression of MMP-2 and MMP-9 in pre- and postmenopausal patients with polyps, suggesting that their expression could depend on the hormonal status of patients with endometrial polyps and type I endometrial cancer. Both have negative prognostic value in the previously mentioned pathologies [ 3 ]. In cervical cancer, Schröpfer et al confirmed the presence of MMP-2, -3, and -9.…”
Section: Resultsmentioning
confidence: 99%
“…Endometrial cancer (EC) is one of the most common malignancies of the female genital system and the sixth most common type of all cancers worldwide [ 1 , 2 , 3 ]. The incidence is higher in developed countries, presumably due to the higher prevalence of obesity and an increase in life expectancies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature provides examples of combining the TMA method with digital image analysis [38]. The TMA method is used in relation to endometrial cancer [39,40]. Most of the previous studies on endometrial cancer showing TNP (+) used the TMA technique [7][8][9]11].…”
Section: Discussionmentioning
confidence: 99%